AUGMENTED REALITY SEBAGAI MEDIA PEMBELAJARAN SEJARAH KERAJAAN HINDU BUDHA DI INDONESIA - RIZQA SUNGADI, ORISKO GEPTNA; Pangaribuan, Hotma (LPPM Universitas Putera Batam, 2023)
This study aims to evaluate the effectiveness of using Augmented Reality technology as a learning media for the history of Hindu-Buddhist kingdoms in Indonesia. This research uses the method of developing Augmented Reality applications that are applied to students at SMK 2 Batam as research subjects. The results of the study show that the implementation of Augmented Reality technology can increase students' interest and learning outcomes in learning the history of Hindu-Buddhist kingdoms. Therefore, it can be concluded that Augmented Reality technology can be used as an effective learning media in learning the history of Hindu-Buddhist kingdoms in Indonesia.